RGD Forever!-Past, Present, and Future of a 3-Letter-Code in Radiopharmacy and Life Sciences - Johannes Notni (MDPI AG, 2022)
"RGD" is frequently pictured as a ligand for αvβ3-integrin and useful for molecular targeting of angiogenesis-which is about as simplistic as the idea that laser beams are green or red and particularly useful for arming spaceships. There is, however, much more to RGD. In particular, targeting angiogenesis is likely not the most significant stronghold of RGD-comprising constructs. RGD is the one-letter code of a very short peptide sequence, arginine-lysine-aspartate, which is recognized by eight different integrins, namely, α(IIb)β3, α5β1, α8β1, and the five dimers that αv forms with β1, β3, β5, β6, and β8. These 8 RGD receptors form an own subset among the entire class of 24 known integrins, which furthermore comprises another three distinct groups (4 collagen receptors, 4 laminin receptors, and 8 leukocyte receptors). However, the 8 RGD-recognizing integrins are far from being alike. They do not even share the same tissue prevalences and functions, but are expressed on fundamentally different cell types and fulfill the most diverse biological tasks. For example, α(IIb)β3 is found on platelets and mediates thrombus formation, whereas αvβ6- and αvβ8-integrin are expressed on epithelial cells, activate TFG-β, and thus may promote cancer progression and invasion as well as fibrosis. Recent non-clinical experiments and clinical findings suggest that the highly specific expression of αvβ6-integrin by some carcinoma types, in combination with the availability of the corresponding small-molecule ligands, may open a multitude of new and promising avenues for improved cancer diagnosis and therapy, including, but not limited to, radiopharmaceutical approaches.